DEVELOPMENT OF THE SKILLS OF HEADS OF SECONDARY SCHOOLS TO ELIMINATE CONFLICTS IN THE PEDAGOGICAL COMMUNITY (Academia Science Repository, 2023)
A study of the skills of heads of secondary schools to eliminate conflicts in the pedagogical community. The leader should be able to diagnose each of the members of the pedagogical team with the dynamics of development. Activities in this direction are also considered necessary to ensure management efficiency.